Japanese FOR DUMMIES - Sato, Eriko, 1962-, author 637958 (Hoboken, N.J. : John Wiley & Sons, Inc, 2013)
Author and Professor of Japanese Eriko Sato introduces the essentials of Japanese grammar and pronunciation, giving you a working sense of the Japanese language, before showing you Japanese in action. You'll also discover social customs, formalities, and manners, from how and when to bow to how to unwrap a present. Includes vocabulary summaries, a mini-dictionary, and an audio CD full of conversations and pronunciations.